Sebaran Residu Insektisida Parathion pada Lahan Pertanian Bawang Merah di Kecamatan Wanasari Kabupaten Brebes - Indratin Indratin; Mochamad Arief Budihardjo; Muhammad Helmi (xxxx-xxxx, 2020)
Indratin I, Budihardjo MA, Helmi M. 2020. Distribution of parathion insecticide residue in shallot agriculture land in wanasari sub-district, Brebes regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The use of pesticides in agricultural land tends to be excessive because farmers think that pesticides can increase yields. It can also pollute the environment. Many farmers often use organophosphate insecticides as the efforts in controlling the pests of shallot plant organisms, one of which is Parathion. The use of Parathion has been banned by the Indonesian government since 2015 for agriculture. This research aims to determine the distribution of Parathion residue in the lower red agricultural land in Wanasari sub-district, Brebes Regency. The research was carried out in March - July 2020 in Wanasari sub-district. Soil samples were taken to the Integrated Laboratory of the Indonesian Agricultural Environment Research Institute to be analyzed the residual content of Parathion by using the QueCheRS method. The mapping of the residue distribution method used ArcGIS 10.4 with the Spline interpolation method. The results of laboratory analysis identified the residual content of Parathion between <LoD : 0.0025 mg kg-1 to 0.0956 mg kg-1. The residual content of the Parathion which was identified to exceed the LoD value was spread over 17 soil sampling points, all identified below the MRLs  value. The identified land area in the very low category was 806.08 ha and identified as low was 1,563.81 ha. The distribution of parathion residues in shallot agricultural land in Wanasari sub-district was identified in the very low and low categories, this needs to be watched out for because it is possible for the farmers to still use parathion type insecticides in shallot cultivation.